Fearing Failure: Grandiose Narcissism, Vulnerable Narcissism, and Emotional Reactivity in Children. Issue 3 (4th June 2019) - Derry, Kate L.; Ohan, Jeneva L.; Bayliss, Donna M.
Abstract : The distinction between grandiose and vulnerable narcissism is new to the child literature, but initial findings suggest that it may have important implications for understanding adjustment. This study examined how expressions of narcissism in children influence their reactions to a mild egothreats experience. Children ( N  = 124; aged 8–12 years) completed self‐ratings before and after doing a brief but challenging task. Negative emotions, self‐conscious emotions, and performance estimates were measured. Regression analyses showed that, even after controlling the effects of self‐esteem and temperament, vulnerable narcissism was related to increased hostility, anger, and shame, whereas grandiose narcissism was related to inflated performance estimates following the task. These results demonstrate the unique roles of grandiose and vulnerable narcissism in children.